Roth and celebrity - Pozorski, Aimee L. (Aimee Lynn) (Lexington Books, 2012)
Roth and Celebrity is composed of 10 original essays that consider the vexed and ambivalent relationship between Philip Roth and his own celebrity as revealed both in personal interviews as well as in the fiction that spans his publishing history. With its simultaneous interest in American popular culture and the work of the most important living American writer to-date, the collection will hold wide appeal to advanced readers in American studies, literary scholarship, and film.